RANCANG BANGUN SISTEM MONITORING NILAI pH DAN KADAR KEKERUHAN AIR PADA KOLAM TERNAK KODOK LEMBU BERBASIS IoT - Dharma Yasa, Ketut; Janardana, I Gusti Ngurah; Budiastra, I Nyoman (Jurnal SPEKTRUM; Vol 7 No 2 (2020): Jurnal SPEKTRUM, 2020)
Frog thigh meat is one of the potential non-oil and gas export commodities. In 2011-2012 the value of frog thigh meat exports decreased from 4.152 tons to 2.694 tons. The scarcity of toads available is due to massive hunting and the spread of red leg syndrome. Red leg syndrome is caused due to lack of monitoring of the condition of the bull frog pond. A harassment solution is needed by utilizing the Internet-based technology of Things as an effort to create an environment, especially the right water content of the bull frog, so as to reduce the number of bull frogs affected by the disease. This tool is able to monitor pH values and water turbidity levels in aquaculture ponds through the Thingspeaks platform. The test was carried out in one of the Beetle Fodder Animal Husbandry Groups located in Buduk Village, Mengwi District, Badung Regency. It was found that the pH value in the pond was 6.5-8 and the turbidity level was 3,8-9 NTU. Based on these results, aquaculture ponds are in accordance with water standards for the life of a bull toad with a pH value of 6.5-8.5 and turbidity levels of 1.2-11.6 NTU